DURASI PENGGUNAAN GADGET TERHADAP NYERI LEHER PADA MAHASISWA DI MASA PANDEMI COVID-19 - Nurhikmah Hikmah; Nurwahida Puspitasari (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
The COVID-19 pandemic has an impact on the world of education. Thus, colleges or universities take alternative learning that is carried out online or commonly reffered to as study from home. This policy greatly affects the use of gadgets for university students because the learning process, which is deal with gadgets every day and will take longer time than usual. This can trigger musculoskeletal disorders, one of which is neck pain. The purpose of this study was to determine the relationship between the duration of gadget use on neck pain in university student during the COVID-19 pandemic. This research method an analytical observational with cross sectional time approach. Respondents in this study were physiotherapy students with a total population of 695 students with inclusion criteria is students aged 18-25 years. The sample in this study was taken by purposive sampling technique and the sample size was determined by the Slovin formula, totaling 88 students. The duration of gadget use was measured by category and neck pain was measured using the neck disability index. The data were analyzed using the Spearman Rank test of the duration of gadget use and neck pain complaints were p=0.588 (p>0.05) with (CC=0.059). The conclusion is that the long duration of using gadget cannot increase the occurrence of neck pain in  university students during the COVID-19 pandemic and the correlation is very weak.